Early rosette mutant plants of safflower (Carthamus tinctorious L.): Early rosette mutant plants of safflower (Carthamus tinctorious L.) - RAJEEV SHRIVASTAVA; S MONDAL (Journal of Oilseeds Research, 2020)
Many high yielding safflower varieties with maturity duration of 140-145 days or more have rosette period ranging from 22-40 days. It was thought to convert high yielding varieties of safflower in to less rosette period genotypes, without reducing yield and oil content. For this if hybridization were applied it affects many other important traits. Therefore, in high yielding varieties/genotypes radiation were applied to create variation and genotypes with reduced rosette period. The mutants with less rosette period as compare to normal genotypes were selected in M2 generation and tested for their stability in M3 generation. In present study in A-1 and other genotypes, mutants were obtained having 15-20days less rosette than normal genotypes.